Efek Jumlah Dewan Direksi dan Komite Audit Terhadap Nilai Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia - Rusnaidi; Tarmizi; Rizki Munazar (Jurnal EMT KITA, 2022)
This study aims to examine the effect of the number of boards of directors and the number of audit committees on firm value. This research is a sample study, which includes 111 manufacturing sector companies during the 2017-2019 observation year with certain criteria. The analytical method used is the fixed effect panel data regression model. The results of this study found that the number of the board of directors has a positive and significant effect on firm value. While the number of audit committees had a not significant effect on firm value.